Students’ Engagement in EFL Online Classrooms during COVID-19 Pandemic: Voices from An Indonesian Private University - Mukminatus Zuhriyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesian education implemented online learning, including EFL online learning, since March 2020. But, the online implementation faced some challenges. One of them was the students’ learning engagement. That was why this study was interested in exploring the students’ engagement in their EFL online classrooms during COVID-19 pandemic. This study used a descriptive qualitative research design to investigate the students’ learning engagement. The participants of this study were forty students of an English education departement in a private university in East Java. Then, the researcher used three research instruments for collecting the data, such as questionnaires, class observation, and interview. The questionnaires related to the students’ behavioural, emotional, and cognitive engagement were administered to the students through Google Form. For the class observation, the researcher joined two online classes. Besides, the researcher also interviewed the lecturer of those two online classes. After the data of questionnaires were tabulated and the class observation data and the interview data were transcripted and coded, the researcher could know the results of this study. The results told that the students had low behavioural, emotional, and cognitive learning engagement during their online learning. Hopefully, the results of this study can give the new consideration for EFL teachers in selecting the teaching strategies and online platform when teaching English remotely.